The effect of cyclic rifaximin therapy on symptoms of diverticular disease from the perspective of the gastroenterology outpatient clinic: a “real-life” study - Moniuszko, Andrzej; Rydzewska, Grażyna (Gastroenterology Review/Przegląd Gastroenterologiczny, 2017)
Introduction: Symptomatic uncomplicated diverticular disease of the colon (SUDD) is one of the most common diseases with which patients present to a gastroenterologist. Mild forms of diverticulitis can also be treated using rifaximin. Although numerous randomised controlled trials have already demonstrated the efficacy of rifaximin therapy, there is still a lack of data from daily medical practice. Aim : To assess the effect of rifaximin on the symptoms of diverticular disease (SUDD and mild diverticulitis) in patients undergoing routine treatment in gastroenterology outpatient clinics in Poland. Material and methods : The retrospective study included 142 patients with a diagnosis of SUDD and mild diverticulitis, with a mean age of 60–69 years (41%), of whom 65% were women. Patients underwent three cycles of rifaximin therapy at a dose of 2 × 400 mg daily for 7 days over 3 consecutive months. Survey data were collected during monthly clinic appointments using a questionnaire completed by 48 gastroenterologists, and in selected cases standard inflammatory parameters were also determined. Results : After just one cycle of therapy a significant reduction in disease symptoms was observed (abdominal pain, abdominal tenderness, bloating, disturbances in bowel habit), defined over a scale of 0–3 points. The mean intensity of symptoms decreased from 1.7 ±0.7 to 0.8 ±0.3 points (with a maximum symptom intensity of 3.0 points). After three cycles, the severity of symptoms decreased markedly to an average of 0.3 ±0.1, and as many as 75% of patients reported no abdominal pain (previously the percentage was only 4%). These differences were statistically significant, p < 0.001. The decrease in inflammatory parameters (white blood cell count, C-reactive protein and erythrocyte sedimentation rate) was statistically significant. Conclusions : Rifaximin is highly effective in the symptomatic relief of uncomplicated diverticular disease of the large bowel, and it is also effective in the treatment of mild forms of diverticulitis. Although the effects were already visible after the first cycle of therapy, the highest efficacy was obtained after three cycles of therapy. Rifaximin can be successfully used in routine medical practice.